PERAN SUPERVISI AKADEMIK MEMODERASI PENGARUH DISIPLIN DAN MOTIVASI TERHADAP KINERJAGURU (STUDI KASUS GURU SMP NEGERI 05 SUB RAYON 05 KOTA SEMARANG) - Suryo Purwanti, 1352020011 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to analyze The Role Of Academic Supervision Moderate The Influence Of Discipline And Motivation On The Performance On Secondary School Teachers In Distric Trunk. In this study is 139 respondentsÂ this study isÂ explanatory research. By all the criteria of senior high school SMP Negeri Sub Rayon 05 teachers Semarang. Measurements use a likert scale of five alternative answers. Test instruments used are validity and reliability. While the test model used is the coefficient of determination and F test (Goodness of Fit). Hypothesis test used in this study usesÂ regression analysis. Based on the results of the study can be summarized as follows: Discipline positive and significant impact on teacher performance, Motivation effect no effect on teacher performance, Academic Supervision positive and significant impact on teacher performance, Academic Supervision doesnât moderate influence discipline on teacher performance, Academic Supervision doesnât moderate influence motivation on teacher Performance. Keywords: Discipline, motivation, teacher performance, and Academic Supervision